Acute intraoperative effect of intravenous amiodarone on right ventricular function in patients undergoing valvular surgery. Issue 4 (August 2015) - Denault, André Y; Beaulieu, Yanick; Couture, Pierre; Haddad, Francois; Shi, Yanfen; Pagé, Pierre; Levesque, Sylvie; Tardif, Jean-Claude; Lambert, Jean
Background: Amiodarone is commonly used in the acute care setting. However the acute hemodynamic and echocardiographic effect of intravenous amiodarone administered intraoperatively on right ventricular (RV) systolic and diastolic function using transesophageal echocardiography (TEE) has not been described. Methods: The study design was a randomized controlled trial in elective cardiac surgical patients undergoing valvular surgery. Patients received an intravenous loading dose of 300 mg of either amiodarone or placebo in the operating room, followed by an infusion of 15 mg/kg for two days. Hemodynamic profiles, echocardiographic measurement of RV and left ventricular (LV) dimensions, Doppler interrogation of tricuspid and mitral valve, hepatic and pulmonary venous flow combined with tissue Doppler imaging of the tricuspid and mitral valve annulus were obtained before and after bolus. Results: Although more patients in the placebo group had chronic obstructive lung disease (14 vs 6, p= 0.05) and diabetes (14 vs 5; p= 0.0244), there was no difference in terms of baseline hemodynamic, 2D and Doppler variables. After bolus, a significant increase in pulmonary artery pressure, central venous pressure and pulmonary vascular resistance index ( p< 0.05) was observed in the amiodarone group with reduction in systolic to diastolic (S/D) ratio of the hepatic ( p= 0.0247) and pulmonary venous ( p =0.0052) velocity. Conclusion: Acute administration of amiodarone is associated with alteration in RV diastolic properties and has minimal negative inotropic effect on RV systolic function in cardiac surgical patients with valvular disease.